FORMULASI LIP CREAM EKSTRAK KULIT JERUK KALAMANSI (Citrofortunella microcarpa L.) SEBAGAI PELEMBAP DAN SARI UMBI BIT (Beta vulgaris L.) SEBAGAI PEWARNA ALAMI - Yureka Arsimida; Dwi Dominica (Jurnal Farmasi IKIFA, 2024)
A study was conducted on creating lip cream products that include calamansi orange peel extract (Citrofortunella microcarpa L.) and beet root extract (Beta vulgaris L.) to assess their efficacy as natural dyes. The aim was to determine if calamansi orange peel extract and beetroot juice can be utilized in lip cream formulations, evaluate the impact of concentration on the physical characteristics, and assess the effectiveness of beetroot as a natural coloring agent. The study employed experimental methods, using extracts at a 4% concentration and juices at concentrations of 25%, 35%, and 45%. Organoleptic tests, pH tests, stability tests, adhesion tests, spreadability tests, and homogeneity tests were performed, and the results were analyzed every 7 days over a 28-day storage period. The findings indicated that the lip cream preparations exhibited favorable organoleptic properties and a suitable pH range of 4.6-6.9. However, they demonstrated poor stability as evidenced by changes in color on the 7th day of storage, although they had good adhesion, spreadability, and homogeneity during storage. The research confirmed that calamansi orange peel extract and beet root extract can be incorporated into lip cream formulations and can influence color characteristics. The change in color of the preparation, from its initial red color to a brownish hue on the 7th day of storage, can possibly be attributed to factors such as temperature, light, oxygen, and pH.